2001
DOI: 10.1063/1.1368377
|View full text |Cite
|
Sign up to set email alerts
|

Wafer bonded 1.55 μm vertical-cavity lasers with continuous-wave operation up to 105 °C

Abstract: We report 105°C continuous-wave, electrically pumped operation of a 1526 nm vertical-cavity surface-emitting laser. An InP/InGaAsP active region was wafer bonded to GaAs/AlGaAs mirrors, with a superlattice barrier to reduce the number of nonradiative recombination centers in the bonded active region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Efficiency and high speed at low power in VCSEL with wavelength of 850-980 nm are a suitable light source for vast application in short-haul such as Gigabit Ethernet. Longer wavelength at 1300-1500 nm permit higher bit rates over longer distances such as optical communication networks [4].…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency and high speed at low power in VCSEL with wavelength of 850-980 nm are a suitable light source for vast application in short-haul such as Gigabit Ethernet. Longer wavelength at 1300-1500 nm permit higher bit rates over longer distances such as optical communication networks [4].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a robust aperturing technique on InP similar to the lateral oxidation of AlGaAs on GaAs has also slowed the rate of progress in long-wavelength VCSEL development. The best high-temperature results to date have been achieved using wafer bonded GaAs-AlGaAs distributed Bragg reflectors (DBRs) in both electrically pumped [5] and optically pumped [6] designs. The high thermal conductivity and index contrast available in the GaAs-AlGaAs material system make it an attractive choice for fabricating long-wavelength VCSEL DBRs.…”
Section: Introductionmentioning
confidence: 99%
“…Early work on electrically pumped wafer-bonded VCSELs suffered from p-type free-carrier losses and large voltage drops at the p-p bonded interface [9]. The work of [2] and [3] circumvented this problem by introducing a vertically integrated 850-nm optical pump and a completely undoped 1310-nm VCSEL.…”
mentioning
confidence: 99%
“…ECENT YEARS have seen a rich variety of approaches to long-wavelength vertical-cavity surface-emitting lasers (VCSELs) [1]- [9]. Both epitaxial mirror approaches and wafer-bonded mirror approaches have achieved room-temperature continuous-wave (RTCW) powers in the neighborhood of 1 mW or greater, and a few authors have reported continuous-wave (CW) lasing beyond 100 C [1]- [4].…”
mentioning
confidence: 99%